Komunikasi Interpersonal antara Pembina dan Anak Jalanan dalam Memotivasi di Bidang Pendidikan dan Mengubah Perilaku di Rumah Singgah Anak Mandiri Yogyakarta (Studi pada anak jalanan di Rumah Singgah Anak Mandiri Yogyakarta) - Dyah Rachmawaty Utami; Christina Rochayanti; Edwi Arif Sosiawan (Jurnal Paradigma, 2012)
Homeless boy emerged because of the low of economy, lack of attention and affection from their parents. Many things that the public did not know about the street children’s life had something interested to be observed. Their education and behavior became a major problem to note. As the condition above Rumah Singgah Anak Mandiri tried motivate the street children in the education filled and change their behavior. Based on the background, the problem of this research was “how do the interpersonal communication between founder and the street children in the field of education motivation and the attitude changing at Rumah Singgah Anak Mandiri Yogyakarta?”. The aims o this research were to know the interpersonal communication between founder and the street children in Rumah Singgah Anak Mandiri. The subjects of this research were founder, street children, and the manager of Rumah Singgah Anak Manandiri Yogyakarta.This research was descriptive qualitative design. The data were taken, analyzed quantitatively and presented by detail and systematic description. The result of this research shows that interpersonal communication between founder and the street children in motivating them in the education field and changing the children’s behavior is not effective enough. It is based on the result of observation can be seen from the aspect of interpersonal communications which cannot be applied maximally are understandings, positive and same vision attitude. Sometimes the process of communication does not receive perfect feedback from communicant. As the reason of that, the researcher feels the interpersonal communication that conducted between fonder and the street children need to be improved the quality and quantity.